Post Hypertension and Stroke: A Case Control Study - Imanda, Aulia; Martini, Santi; Artanti, Kurnia Dwi (UI Scholars Hub, 2019)
The purpose of this study was to determine the factors that influence the incidence of stroke including smoking status, past hypertension , past diabetes, diet, physical activity, alcohol consumption. The design of this study is case control with a ratio of 1: 1. The total number of respondents is 132 people. Research subjects were selected using systematic random sampling. This research was conducted at Ngudi Waluyo Hospital in Wlingi. Blitar, Indonesia in October till November 2017. Bivariate analysis showed that factors significantly related to stroke were smoking status (p=0.011, OR=2.6), history of past hypertension (p=0.00, OR= 6), past diabetes (p=0.015 ; OR=5,7), and unhealthy diet (p= 0,00; OR = 5,7). Multivariate analysis showed that factors that significantly influence stroke are smoking, having hypertension in the past, and unhealthy diet. Conclusion of this study was smoking, having hypertension in the past, and unhealthy diet are factors that influence the incidence of stroke. Maintaining normal blood pressure, maintaining a diet, and not smoking are precautions should be taken in order to prevent stroke.